A fluorescent "glue" of water triggered by hydrogen-bonding cross-linking. Issue 47 (28th October 2016) - Wang, Dejia; Zhao, Hongwei; Li, Hongjuan; Sun, Shiguo; Xu, Yongqian
Abstract : As a "glue" of water, a small organic molecule with the novel hydrogen-bonding cross-linked aggregation-induced emission (AIE) property was designed to detect trace water, displaying a wide linear range (0–40%, v/v) in most of the organic solvents. Abstract : As a "glue" of water, a small organic molecule with the novel hydrogen-bonding cross-linked aggregation-induced emission (AIE) property was designed to detect trace water, displaying a wide linear range (0–40%, v/v) in most of the organic solvents. The molecule shows strong stability under different conditions (pH, ionic strength and dissolved oxygen). More importantly, the molecule demonstrated its potential application for the detection of humidity, water-jet printing and collection of fingerprint information.